Effect of blend ratio on poly(p-phenylene-ethynylene)-alt-poly (p-phenylene-vinylene) polymer solar cell - Tore, Nesrin; Parlak, Elif Alturk; Usluer, Ozlem; Egbe, Daniel A. M.; San, Sait E.; Aydogan, Pelin (ELSEVIER, 2012)
We investigated the effect of the amount of phenyl C-61 butyric acid methyl ester (PCBM) on anthracene-containing poly(p-phenylene-ethynylene)-alt-poly(p-phenylene-vinylene) (PPE-PPV) polymer (AnE-PVstat) solar cells. The efficiencies and fill factors of the polymer solar cells improved with increasing PCBM content. The highest efficiency obtained was 2.13% for AnE-PVstat:PCBM solar cells with 75% PCBM content. The increased efficiency for that PCBM content can be attributed to a change in the thin film nanostructure. The normalized efficiency values versus time plot from ISOS-L-1 test indicated that the AnE-PVstat:PCBM solar cell with 1:2 blend ratio showed 100% durability; for 1:3 and 1:4 ratios it showed with approximately 96% durability under standard solar irradiation of 100 mW/cm(2) (AM1.5G) at ambient conditions for 21 h. ISOS-D-3 Damp test indicated that the normalized j(sc) and normalized efficiency versus time graphs showed similar behaviors: the AnE-PVstat:PCBM solar cell with 1:4 ratio has 99% durability for 40 h in a weathering chamber. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: AnE-PVstat; Polymer solar cell; Blend ratio; INTERNAL QUANTUM EFFICIENCY; ALKOXY SIDE-CHAINS; PHOTOVOLTAIC PERFORMANCE; CONJUGATED POLYMERS; MORPHOLOGY; PCBM; Energy & Fuels; Materials Science; Physics